Security in SDN networks and their applications - Tapiero Tapiero, Robin Estid; Cerquera González, Edward Alejandro; Novoa Torres, Norberto (Ingeniería Solidaria, 2021)
Introduction: The review article is the product of the research on Security in SDN networks and their applications, developed at the District University in 2020, presenting the latest advances, that have been made in security. Problem: The security weaknesses that SDN networks have had, due to being a new architecture. This has not allowed traditional networks to be replaced. Objective: To carry out a review of the state of the art of SDN networks, focusing research on the security of the control layer and its advances. Methodology: The descriptive method is implemented, consulting databases such as Scopus, IEEE and ScienceDirect, using the following search criteria: SDN networks, security in SDN networks, applications with SDN networks and OpenFlow protocol. It is shown as a research sample: the Asian, European and American continents with years of research from 2014 to 2020. Results: Great advances have been made in terms of security for SDN networks, which allows us to see an early solution to the weaknesses that it currently faces. Conclusion: SDN networks will solve all the challenges they face and will be consolidated as a solid and reliable architecture. Originality: an important focus is taken on the security of SDN networks and the great development that has occurred in this regard is evident. Limitations: SDN networks are a new architecture, so their development has been very little and advances in security have been significantly affected.